Association between urologic malignancies and end‐stage renal disease: A meta‐analysis. Issue 1 (16th December 2018) - Kompotiatis, Panagiotis; Thongprayoon, Charat; Manohar, Sandhya; Cheungpasitporn, Wisit; Gonzalez Suarez, Maria L; Craici, Iasmina M; Mao, Michael A; Herrmann, Sandra M
ABSTRACT: Aim: Previous studies have suggested a higher incidence of urologic malignancies in end‐stage renal disease (ESRD) patients. However, incidence trends of urologic malignancies in ESRD patients remain unclear. The aims of the present study were: (i) to investigate the pooled incidence/incidence trends; and (ii) to assess the risk of urologic malignancies in ESRD patients. Methods: A literature search was conducted using MEDLINE, EMBASE and Cochrane Database from inception through April 2017. Studies that reported incidence or odds ratios of urologic malignancies among ESRD patients were included. Pooled odds ratios (OR) and 95%CI were calculated using a random‐effect model. The protocol for this meta‐analysis is registered with PROSPERO (International Prospective Register of Systematic Reviews; no. CRD42017067687). Results: Nineteen observational studies with 1 931 073 ESRD patients were enrolled. The pooled estimated incidence of kidney cancer and urothelial cancers (carcinomas of the bladder, ureters, and renal pelvis) in ESRD patients were 0.3% (95%CI: 0.2–0.5%) and 0.5% (95%CI: 0.3–0.8%), respectively. Meta‐regression showed significant positive correlation between incidence of urologic malignancies in ESRD patients and year of study (slopes = +0.05 and +0.07, P < 0.001 for kidney cancer and urothelial cancers, respectively). Compared to non‐ESRD status, ESRD was significantly associated with both kidney cancer (pooled OR 6.04; 95% CI 4.70–7.77) and urothelial cancers (pooled OR 4.37; 95% CI 2.40–7.96). Conclusion: Our study demonstrates a significant association between ESRD and urologic malignancies. The overall estimated incidence rates of kidney cancer and urothelial cancers are 0.4% and 0.5%, respectively. There is a significant positive correlation between the incidence of urologic malignancies and year of study. Summary at a Glance: This paper examines the association of ESKD and urinary tract malignancies, with malignancy occurrence rates four to six times higher in ESKD compared to the general population.